The Complex Puzzle of Interactions Among Functional Food, Gut Microbiota, and Colorectal Cancer - Mendonça, Lígia A. B. M.; dos Santos Ferreira, Rosângela; de Cássia Avellaneda Guimarães, Rita; de Castro, Alinne P.; Franco, Octávio L.; Matias, Rosemary; Carvalho, Cristiano M. E. (Frontiers in Oncology, 2018)
Colorectal cancer exerts a strong influence on the epidemiological panorama worldwide, and it is directly correlated to etiologic factors that are substantiated by genetic and environmental elements. This complex mixture of factors also has a relationship involving the structural dependence and composition of the gut microbiome, leading to a dysbacteriosis process that may evolve to serious modifications in the intestinal lining, eventually causing the development of a neoplasm. The gastrointestinal tract presents defense strategies and immunological properties that interfere in intestinal permeability, inhibiting the bacterial translocation, thus maintaining the integrity of intestinal homeostasis. The modulation of the intestinal microbiome and the extinction of risk factors associated with intestinal balance losses, especially of environmental factors, make cell and defense alterations impossible. This modulation may be conducted by means of functional foods in the diet, especially soluble fibers, polyunsaturated fatty acids, antioxidants and prebiotics that signal immunomodulatory effects in the intestinal microbiota, with preventive and therapeutic action for colorectal cancer. In summary, this review focuses on the importance of dietary modulation of the intestinal microbiota as an instrument for dysbacteriosis and, consequently, for the prevention of colorectal cancer, suggesting anticarcinogenic and antiangiogenic properties. Among the intestinal modulating agents considered here are functional foods, especially flaxseed, oat and soy, composing a Bioactive Food Compound.